A comprehensive study of infrastructure failures in the energy industry to improve operational safety - Ardyrizky, Dhanies Wahyu; Prabowo, Aditya Rio; Baek, Seung Jun; Do, Quang Thang (Universitas Negeri Semarang, 2025)
The demand for crude oil continues to increase in line with expanding needs, but this contrasts with its limited availability in nature. The oil and gas industry is one of the key sectors in the global economy, encompassing exploration, refining, processing, transportation, distribution, and sales. Given the high-risk working environment, safety is a crucial factor that must be considered. In recent decades, numerical methods have been widely used to enhance the effectiveness and efficiency of safety analysis, particularly in risk identification, equipment condition monitoring, and optimizing hazard mitigation strategies. This report discusses the application of numerical methods in improving the quality of planning, maintenance, and failure mitigation of various components and infrastructure at PT Pertamina Patra Niaga Fuel Terminal Boyolali. The study focuses on MOV with the friction coefficient between the stem and stem nut, pipeline systems concerning corrosion in elbows caused by chemical compounds carried by oil, and storage tanks related to temperature control within the tank to maintain the quality and quantity of oil as per demand. A comprehensive study shows that lubrication can limit the friction coefficient in MOV, while viscosity is a significant issue in pipeline systems and storage tanks. Numerical approach methods can improve the energy industry's safety, reliability, and efficiency. Modeling can reduce costs, time, and worker safety risks compared to experimental approaches.